Hydrological changes during the Roman Climatic Optimum in northern Tuscany (Central Italy) as evidenced by speleothem records and archaeological data. (15th June 2020) - Bini, M.; Zanchetta, G.; Regattieri, E.; Isola, I.; Drysdale, R. N.; Fabiani, F.; Genovesi, S.; Hellstrom, J. C.
ABSTRACT: Study of the climate in the Mediterranean basin during different historical periods has taken on a particular importance, particularly regarding its role (together with other factors) in the evolution of human settlement patterns. Although the Roman age is traditionally considered a period with a favourable climate, recent studies have revealed considerable complexity in terms of regional climate variations. In this paper, we compare the hydrological change from speleothem proxy records with flood reconstructions from archaeological sites for Northern Tuscany (central Italy). We identify a period of oscillating climatic conditions culminating in a multidecadal dry event during the 1st century bc, followed by a century of increased precipitation at the beginning of the Roman Empire and subsequently a return to drier conditions in the 2nd century ad. The period of rainfall increase documented by the speleothems agrees with both the archaeological flood record as well as historical flood data available for the Tiber River, ca. 300 km to the south. These data also suggest a return to wetter conditions following the 3nd and 4rd centuries ad.